Global Citizenship and Women's Empowerment Among Indonesian Female Participants in The King Salman Global Academy Program in Saudi Arabia - Aulia Sholichah Iman Nurchotimah; Alif Aditya Candra; Rijal Assidiq Mulyana (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
Women's participation in international educational programs has become an important pathway for promoting women's empowerment and strengthening global citizenship. Despite increasing opportunities for international mobility, women often negotiate academic aspirations alongside family responsibilities and social expectations. This study examines how participation in the King Salman Global Academy (KSGA) Arabic Language and Culture Program contributed to the development of global citizenship and women's empowerment among Indonesian female participants. A qualitative case study was conducted involving six Indonesian women from diverse professional backgrounds, including lecturers, teachers, and a legal studies graduate. Data were collected through participant observation, reflective documentation, and semi-structured interviews during the eight-month program in Riyadh, Saudi Arabia, from October 2025 to May 2026. Data were analyzed using thematic analysis. The findings indicate that participants joined the program to enhance Arabic language proficiency, expand international networks, gain intercultural learning experiences, and support their professional development. Interactions with participants from various countries strengthened intercultural competence, fostered global citizenship, and encouraged participants to promote Indonesian culture through cultural presentations, food exchanges, and collaborative activities. Although participants experienced challenges related to family separation and domestic responsibilities, they reported increased self-confidence, improved Arabic and English language skills, broader global perspectives, and stronger professional aspirations. These findings demonstrate that international educational programs function as transformative spaces for advancing both women's empowerment and global citizenship.